Tracing fcc iron in oxide dispersion strengthened steel by photoelectron emission, Mössbauer spectroscopy, and X-ray diffraction. (May 2020) - Pető, G.; Dézsi, I.; Kiss, L.F.; Horváth, Z.E.; Oszetzky, D.; Nagy, A.; Molnár, G.; Daróczi, Cs.S.; Frey, K.; Horváth, A.
Abstract: The crystal structure, the magnetic properties, and the valence band density of states of an oxide dispersion strengthened (ODS) steel with nominal composition of Fe–18%Cr–13%Ni-2.5%Mo-3.2%Si-0.1%C +1 wt% Y2 O3 was investigated applying volumetric and surface sensitive methods. The sample volume contained majority fcc and minority bcc phases according to XRD and volumetric magnetic measurements, while the top layer of the grains contained only the paramagnetic fcc phase, revealed by conversion electron Mössbauer spectrometry (CEMS) and by photoelectron measurements. The valence band photoelectron emission spectra reflected well the average distribution of the theoretically expected DOS, however, there were no signs of abrupt peaks in the region of 0–4 eV below the Fermi level that could have been attributed to 3d Fe states (bcc phase). It was demonstrated that the photoelectron emission can be utilized to distinguish the Fe atoms located in different crystallographic structures. The valence band data of the ODS steel was compared to that of originating from a bcc iron based magnetic alloy. Highlights: The volume of our ODS steel contained majority fcc and minority bcc phases. In the 60–300 nm thick top layer only the fcc phase was detected. The corrupted Y2O3 oxide coverage could lead to the missing bcc phase. Valance band photoelectron emission of the Fe supports theoretical calculations.